PENGARUH PELAKSANAAN KELAS IBU HAMIL TERHADAP PENGETAHUAN TENTANG PERSIAPAN PERSALINAN DI DESA TALAGA KECAMATAN MANCAK TAHUN 2023 - Indhawati, Wulan; Tridiyawati, Feva (Jurnal Ilmiah Global Education, 2023)
The program organized by the Ministry of Health to support this step is the class for pregnant women. Class activities for pregnant women use learning methods, one of which is by discussing the material in the MCH book. The use of the MCH handbook is expected to improve the quality of maternal and child health and nutrition services so that one of the national development goals, namely reducing MMR and IMR, can be achieved. Based on the above, the researcher is interested in conducting research entitled "The Influence of Conducting Pregnant Women's Classes on Knowledge About Birth Preparation in Talaga Village, Mancak District in 2023". Research Objectives: To find out the level of influence of holding pregnant women's classes on knowledge about childbirth preparation. Research Methods: This study used a quasi-experimental with purposive sampling with a sample of 30 people. Data techniques included in univariate analysis using the normalization test and bivariate analysis using the SPSS program statistical calculations. Research results: The results of the Paired Sample Test show that the Sign (2-tailed) value is 0.000 <0.05, so H0 is rejected and Ha is accepted. So it can be concluded that there is an effect of using the answer gallery learning strategy in leaving learning outcomes for pregnant women classes in Talaga village, Mancak sub-district. Conclusions and Suggestions: There is a significant influence of class knowledge on pregnant women. It is expected that pregnant women can attend classes for pregnant women